Digital literacy curriculum transformation to overcome filter bubble in Pancasila character understanding - Achdyat Achdyat; Dasim Budimansyah; Encep Syarif Nurdin; Mupid Hidayat (Himpunan Pengembang Kurikulum Indonesia, 2025)
The rapid development of technology and social media has created a filter bubble phenomenon that limits the diversity of information and threatens national values including the character of Pancasila in the younger generation. This research aims to examine the influence of the filter bubble phenomenon on social media in the context of Pancasila values, as well as formulate effective strategies and transformation of the education curriculum to strengthen awareness of diversity, unity, and mutual cooperation. This research uses a qualitative approach with phenomenological methods to explore participants' subjective experiences and meanings, which are analyzed descriptively through the concept of epoche. The data collection techniques used were observation, interviews, documentation, and questionnaires, then analyzed through data reduction, data presentation, and conclusion drawing. The results show that the bubble filter phenomenon on social media affects the way individuals access and understand information, mainly because algorithms tend to present content that matches personal preferences, thus limiting exposure to alternative perspectives. The impact is seen in the homogenization of information, strengthening of confirmation bias, and polarization of understanding, which has the potential to cause distortion of Pancasila values, so digital literacy, algorithm transparency, and transformation of the education curriculum are needed to overcome it. Abstrak Pesatnya perkembangan teknologi dan media sosial memunculkan fenomena filter bubble yang membatasi keberagaman informasi dan mengancam nilai-nilai kebangsaan termasuk karakter Pancasila pada generasi muda. Penelitian ini bertujuan untuk mengkaji pengaruh fenomena filter bubble di media sosial dalam konteks nilai-nilai Pancasila, serta merumuskan strategi efektif dan transformasi kurikulum pendidikan guna memperkuat kesadaran akan kebhinekaan, persatuan, dan gotong royong. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi untuk mengeksplorasi pengalaman dan makna subjektif partisipan, yang dianalisis secara deskriptif melalui konsep epoche. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara, dokumentasi, dan kuesioner, lalu dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa fenomena filter bubble pada media sosial memengaruhi cara individu mengakses dan memahami informasi, terutama karena algoritma cenderung menyajikan konten yang sesuai dengan preferensi pribadi, sehingga membatasi paparan terhadap perspektif alternatif. Dampaknya terlihat pada homogenisasi informasi, penguatan bias konfirmasi, dan polarisasi pemahaman, yang berpotensi menyebabkan distorsi nilai-nilai Pancasila, sehingga diperlukan literasi digital, transparansi algoritma, serta transformasi kurikulum pendidikan untuk mengatasinya. Kata Kunci: filter bubble; karakter; literasi digital; Pancasila